Interaction of Injector Design, Bubble Size, Flow Structure, and Turbulence in Ladle Metallurgy. Issue 2 (21st September 2018) - Owusu, Kwaku B.; Haas, Tim; Gajjar, Prince; Eickhoff, Moritz; Kowitwarangkul, Pruet; Pfeifer, Herbert
Abstract : In ladle metallurgy, the flow of purge gas through injectors promotes an effective mixing of the melt concerning composition and energy. In this work, different types of gas injectors, positioned eccentrically at 66% of the ladle radius are investigated in terms of the bubble size distribution, the resultant flow field velocity, and turbulent kinetic energy. The experiments are carried out in a 1:3 scale water model of a 185 t ladle using Particle Image Velocimetry (PIV) and image processing. It is shown that a porous plug provides more intensive bulk convection and a higher degree of turbulence than the other tested injectors. The differences are explained by the generation of smaller bubbles, which transfer more momentum into the liquid. The differences between the injectors are small, though. Thus, it is concluded that in comparison with other process parameters, the type of injector plays a minor role in the efficiency of ladle metallurgy. Abstract : The interaction of injector design, bubble size distribution, flow structure, and turbulence in ladle metallurgy are studied with an air‐water model scaled at 1:3 of an industrial 185 t ladle furnace. The flow field velocity and turbulent kinetic energy are visualized by the Particle Image Velocimetry (PIV) measurements whereas the bubble sizes are investigated with a MATLAB image processing technique.